Room-temperature super-elongation in high-entropy alloy nanopillars - Zhang, Qian (2024)
Nanoscale small-volume metallic materials typically exhibit high strengths but often suffer from a lack of tensile ductility due to undesirable premature failure. Here, we report unusual room-temperature uniform elongation up to ~110% at a high flow stress of 0.6-1.0 GPa in single-crystalline <110>-oriented CoCrFeNi high-entropy alloy nanopillars with well-defined geometries. By combining high-resolution microscopy and large-scale atomistic simulations, we reveal that this ultrahigh uniform tensile ductility is attributed to spatial and synergistic coordination of deformation twinning and dislocation slip, which effectively promote deformation delocalization and delay necking failure. These joint and/or sequential activations of the underlying displacive deformation mechanisms originate from chemical compositional heterogeneities at the atomic level and resulting wide variations in generalized stacking fault energy and associated dislocation activities. Our work provides mechanistic insights into superplastic deformations of multiple-principal element alloys at the nanoscale and opens routes for designing nanodevices with high mechanical reliability.